Peningkatan Peran Kader Dalam Pencegahan Stroke Pada Penderita Hipertensi Melalui Family Coaching - Yan, Loriza Sativa; Ernawati, Ernawati (Poltekkes Kemenkes Jambi, 2023)
Stroke can have sequelae and adverse health effects after hospital treatment. Stroke prevention requires good support from all parties, including the family. Health cadres must take a family approach to the stroke care process for clients at home. This community empowerment activity was carried out to increase cadres' knowledge in preventing stroke in hypertension sufferers. Community Development and Empowerment Model was applied in this community empowerment activity. The strategies are implemented in the form of family coaching and health education. The activity partners are 30 PTM (Non-Communicable Disease) cadres. The results of the activity showed that there was an increase in the knowledge and ability of cadres to provide stroke preventative guidance to families who have hypertension sufferers at home.